NALAR AYAT DAN HADITS TENTANG THALAQ DAN PROBLEMATIKA DENGAN THALAQ DI HADAPAN HAKIM - Shabri, Abdurrahman (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2023)
The requirement for a reason for divorce as applied in Indonesia is in accordance with the contents of Surah al-Nisa' (4): 34-35 by using the letter wawu ataf in dalalat al-tartib (showing sequentially), not li mutlaq al-jam'i or li al-mai'yah (together). Therefore, a husband should not immediately say the words talaq to his wife, for example saying